EDUKASI DAN PENDAMPINGAN PEMASARAN PRODUK KERIPIK KENTANG MELALUI PLATFORM E-COMMERCE UNTUK MENINGKATKAN DAYA SAING UMKM DI DESA WATES - F Firdaus; Amrudin Mahfud Jumai; Ari Dwi Astono; M.Roby Jatmiko; Wa Ode Sitti Nurrahmah; M Martini; Sri Sulistiyaningsih; Asepta Hendriyanto; Kukuh Mulyanto; Nuruddin Mahmud (Jurnal AbdiMas Nusa Mandiri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in strengthening the local economy, particularly in rural areas. However, many MSME actors still face limitations in digital marketing capabilities and the utilization of e-commerce platforms. In Wates Village, potato chip MSMEs primarily relied on conventional marketing methods and had not yet adopted digital-based marketing strategies. This community service activity aimed to improve MSME competitiveness through education and mentoring in the use of e-commerce platforms for product marketing. The program employed a participatory training and mentoring approach consisting of socialization, hands-on training, online store creation, product catalog management, product photography, and digital promotion strategies. The activity involved 10 MSME participants, all of whom successfully created and managed online stores on e-commerce platforms. The evaluation results showed a significant increase in participants’ understanding of digital marketing and e-commerce, with the average score increasing from 45 in the pre-test to 82.5 in the post-test, representing an improvement of 83.3%. In addition, participants demonstrated the ability to upload products, create product descriptions, and apply simple digital promotion techniques independently. The program also contributed to increasing product visibility and expanding market access through digital platforms, thereby strengthening the competitiveness of MSMEs in the digital economy era.